Neuromuscular and inflammatory responses to handball small-sided games: the effects of physical contact - Dello Lacono, A.; Eliakim, A.; Padulo, J.; Laver, L.; Ben-Zaken, S.; Meckel, Y. (Scandinavian Journal of Medicine & Science in Sports, 2017)
The aim of this study was to investigate the influence of physical contact on neuromuscular impairments and inflammatory response during handball small-sided games. Using a counterbalanced design, 12 elite male junior handball players were divided into two groups: contact (C-SSG) and no-contact (NC-SSG), performing both contact and no-contact small-sided games, in reverse order on two training sessions separated by 5 days. The methodology and rules were identical for the two SSG regimens, with the only difference being the inclusion or prohibition of upper body use for physical contacts. Upper and lower body neuromuscular performances and blood concentrations of inflammatory cytokine IL-6 were assessed before and immediately after the games. During small-sided games, video analysis was used to establish the physical contact counts. Significant differences were found in most upper and lower limbs muscles kinetic variables and in the physical contact events (all P < 0.001) following the two training regimens. There was an increase in IL-6 after C-SSG and no changes following NC-SSG (P < 0.05 and P = 0.12, respectively). Moreover, a strong correlation was found between the number of physical contacts and IL-6 responses (r = 0.971, P < 0.001) in C-SSG. This study indicates that an inflammatory response and large upper and lower body neuromuscular impairments result from physical contact in elite handball players. These outcomes outline the specific physiological profile of C-SSG that, in turn, might be used by practitioners and coaches as a practical approach to strategically select exercises in athlete's overall training program.